Impact of Medicaid Expansion on Medicaid-covered Utilization of Buprenorphine for Opioid Use Disorder Treatment - Wen, Hefei; Hockenberry, Jason M; Borders, Tyrone F; Druss, Benjamin G (Medical care, 2017)
Buprenorphine has been proven effective in treating opioid use disorder. However, the high cost of buprenorphine and the limited prescribing capacity may restrict access to this effective medication-assisted treatment for opioid use disorder. To examine whether Medicaid expansion and physician prescribing capacity may have impacted buprenorphine utilization covered by Medicaid. We used a quasi experimental difference-in-differences design to compare the pre-post changes in Medicaid-covered buprenorphine prescriptions and buprenorphine spending between the 26 states that implemented Medicaid expansions under the Affordable Care Act in 2014 and those that did not. All Medicaid enrollees in the expansion states and the nonexpansion and late-expansion states. Quarterly Medicaid prescriptions for buprenorphine and spending on buprenorphine from the Centers for Medicare and Medicaid Services Medicaid Drug Utilization files 2011 to 2014. State implementation of Medicaid expansions in 2014 was associated with a 70% increase (P<0.05) in Medicaid-covered buprenorphine prescriptions and a 50% increase (P<0.05) in buprenorphine spending. Physician prescribing capacity was also associated with increased buprenorphine utilization. Medicaid expansion has the potential to reduce the financial barriers to buprenorphine utilization and improve access to medication-assisted treatment of opioid use disorder. Active physician participation in the provision of buprenorphine is needed for ensuring that Medicaid expansion achieves its full potential in improving treatment access.